Newcomer youth’s access to contraception care in Canada: A scoping review of qualitative evidence - Zeba Khan; Bimbola Olure; Victoria Paller; Sarah Munro (PLoS ONE, 2025)
Objective Many newcomer youth in Canada experience high rates of unmet sexual and reproductive health (SRH) care needs, including contraception. We conducted a scoping review of qualitative evidence to understand newcomer youth’s experiences of accessing contraception care in Canada. Design and data sources We followed the Joanna Briggs Institute guidelines to search five databases (MEDLINE, Embase, CINAHL, PsycINFO and Web of Science). Eligibility criteria Qualitative and mixed methods studies describing newcomer youth experiences of SRH in Canada, published in or after 2010 were included. Data extraction and synthesis We adapted relevant headings for our data charting table from the JBI guidelines and a published scoping review on adolescent health. We reported the findings of our analysis as a narrative summary of the included articles. Results We screened 415 titles and abstracts and retrieved 17 eligible studies for full-text review, of which five were included for analysis. Results highlight that sociocultural influences play an important role in newcomer youth’s perspectives and access to contraception care. The language preferences of newcomer youth in the context of contraception are unique and differ from the needs of the broader immigrant population seeking general health care. Results also identify formal and peer-based educational SRH interventions acceptable to newcomer youth. Conclusion Literature that qualitatively describes newcomer youth’s experiences with contraception is scarce, and existing literatures only mentioned contraception in the context of broader SRH-related issues. Further research that specifically focuses on contraception experiences, involves newcomer youth in the research process and explores the roles of peers in contraception access of newcomer youth is required to better understand their experiences.